Analysis of Students’ Speaking Skill at Ninth Grade in Junior High School 2 Jambi City - Tiara Putri Hartanti; Nurul Fitri; Efa Silfia (Universitas Batanghari Jambi, 2022)
This study was conducted with the aim of analyzing students' speaking skills, at ninth grade in Junior High School 2 Jambi City. This research was designed using descriptive quantitative research methods. The population of this study was the ninth-grade students at Junior High School 2 Jambi City, and the sample was grade IX D students. This research uses a test as a research instrument. Then the test results are assessed and. The test used is an oral test with paired dialogue. The dialogue is made with the theme of